A Survey of Photoelectrons on the Nightside of Mars. Issue 2 (25th January 2021) - Cao, Y. ‐T.; Cui, J.; Wu, X. ‐S.; Niu, D. ‐D.; Lai, H. ‐R.; Ni, B. ‐B.; Luo, Q.; Yu, J.; Wei, Y.
Abstract: Despite produced exclusively on the dayside, photoelectrons, as an important population of the Martian ionosphere, have also been observed on the nightside. Here we present a statistical survey of nightside photoelectrons using the suprathermal electron measurements, made by the Solar Wind Electron Analyzer onboard the Mars Atmosphere and Volatile Evolution. We find that nearly 30% of the available nightside suprathermal electron spectra show clear photoelectron signatures. Nightside photoelectrons have an occurrence rate that decreases with increasing solar zenith angle and they are characterized by a preferentially field‐aligned pitch angle distribution. Our analysis also suggests that nightside photoelectrons are less likely observed under the high solar wind condition. These observations are favorably interpreted by the scenario of photoelectron transport along cross‐terminator magnetic field lines, as supported by a simplified test particle model. Our study highlights a complex plasma environment near Mars modulated by both internal and external conditions. Plain Language Summary: Photoelectrons are an important population of a planetary upper atmosphere that plays a crucial role in ionization, heating, radiation, and escape. Despite that photoelectrons are ideally produced by solar radiation on the dayside only, they have also been observed on the nightside of a planet such as Mars. This study is devoted to a statistical survey of photoelectrons in the nightside Martian upper atmosphere, based on the state‐of‐the‐art measurements made by the Mars Atmosphere and Volatile Evolution (MAVEN) spacecraft. A surprisingly large fraction of photoelectron energy spectra is identified on the nightside of Mars, occupying nearly 30% of the available nightside measurements. Meanwhile, substantial variations in the observations of nightside photoelectrons are suggested by the data, revealing that (1) their occurrence rate declines rapidly near and beyond the terminator; (2) their velocities are more likely parallel to the ambient magnetic field lines; and (3) they are less likely observed under high solar wind dynamic pressures. These observations could be interpreted by photoelectron transport along large‐scale magnetic field lines from their dayside source regions to the nightside, a scenario that is controlled by both internal and external conditions and thus provides a useful diagnostic of the ambient magnetic field configuration. Key Points: The photoelectron occurrence rate in the nightside Martian ionosphere decreases with increasing solar zenith angle Nightside photoelectrons are observed to be preferentially field‐aligned, as a natural result of cross‐terminator transport Nightside photoelectrons are more likely observed under low solar wind dynamical pressures